INTEGRATION OF LOCAL ETHNOMATHEMATICS BASED ON ARTIFICIAL INTELLIGENCE (AI) IN ENHANCING STUDENTS’ CRITICAL THINKING SKILLS - Herwandi Sape; Andi Mulawakkan Firdaus; Arwin Wahyu Saputra; Muh. Fachrullah Amal (Almeera Education, 2025)
This study aims to examine the effect of integrating local ethnomathematics based on Artificial Intelligence (AI) on students’ mathematical critical thinking skills. The research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The study was conducted at SMA Negeri 3 Maros, involving 54 eleventh-grade students divided into an experimental class (27 students) and a control class (27 students). The experimental class received mathematics instruction through the integration of local ethnomathematics supported by an AI-based adaptive learning system, while the control class was taught using conventional methods. Data were collected using a critical thinking test administered as pretest and posttest, based on indicators of analysis, evaluation, inference, and conclusion. The results revealed that the experimental class achieved a higher mean posttest score (88.40) compared to the control class (83.20). The N-Gain score of the experimental class (0.78; very high category) was also greater than that of the control class (0.68; high category). Independent samples t-test indicated a significant difference between the two groups (p < 0.05). These findings demonstrate that integrating local ethnomathematics with AI significantly enhances students’ mathematical critical thinking skills and provides an innovative, contextual, and adaptive learning alternative.